Stability and load bearing capacity of a bars with built up cross section and elastic supports = Badania stateczności i nośności prętów złożonych z podporami sprężystymi - Krajewski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present paper is devoted to the numerical analysis and experimental tests of compressed bars with built?up cross section which are commonly used as a top chord of the roof trusses. The significant impact on carrying capacity for that kind of elements in case of out-of-plane buckling is appropriate choice of battens which are used to provide interaction between separate members.
Keywords: przekrój złożony; przewiązka; obciążenie krytyczne; obciążenie graniczne; sztywność podpór; built-up cross section; batten; buckling load; limit load; support stiffness